IMPROVED GREEN'S FUNCTIONS FOR PASSIVE-SOURCE STRUCTURAL STUDIES - Mercier J.-P.; Bostock M.G.; Baig A.M. (My University, 2006)
Over the past two decades, teleseismic receiver functions have proved to be a useful tool to investigate crustal structure. Because they represent a first-order approximation to the S-wave component of the teleseismic-P Green's function, receiver functions provide valuable information on physical properties related to shear modulus. However, the implicit use of the P-component seismogram as a proxy for the source precludes the recovery of information on discontinuous structure involving contrasts in compressional modulus. By deconvolving improved estimates of complex source time functions generated by earthquakes, one may move beyond the conventional receiver function paradigm to a more accurate approximation of the earth's Green's function. Using a new deconvolution method, we present estimates of the P-component of the teleseismic-P Green's functions at several stations of the Canadian National Seismic Network (CNSN) that clearly show the receiver-side pure P-wave crustal multiple. The identification and characterization of these signals in studies of the lithosphere will afford better constraints on subsurface lithology and represent a narrowing of the gap between active- and passive-source seismic imaging. © 2006 Society of Exploration Geophysicists.
Keywords: EARTH CRUST; EARTHQUAKES; GEOPHYSICAL TECHNIQUES; GREEN'S FUNCTION METHODS; SEISMIC WAVES